Heterogeneous alleles comprising G6PD deficiency trait in West Africa exert contrasting effects on two major clinical presentations of severe malaria. (December 2016) - Shah, Shivang; Rockett, Kirk; Jallow, Muminatou; Sisay-Joof, Fatou; Bojang, Kalifa; Pinder, Margaret; Jeffreys, Anna; Craik, Rachel; Hubbart, Christina; Wellems, Thomas; Kwiatkowski, Dominic
Abstract Background Glucose-6-phosphate dehydrogenase (G6PD) deficiency exhibits considerable allelic heterogeneity which manifests with variable biochemical and clinical penetrance. It has long been thought that G6PD deficiency confers partial protection against severe malaria, however prior genetic association studies have disagreed with regard to the strength and specificity of a protective effect, which might reflect differences in the host genetic background, environmental influences, or in the specific clinical phenotypes considered. Methods A case-control association study of severe malaria was conducted in The Gambia, a region in West Africa where there is considerable allelic heterogeneity underlying expression of G6PD deficiency trait, evaluating the three major nonsynonymous polymorphisms known to be associated with enzyme deficiency (A968G, T542A, and C202T) in a cohort of 3836 controls and 2379 severe malaria cases. Results Each deficiency allele exhibited a similar trend toward protection against severe malaria overall (15–26 % reduced risk); however, in stratifying severe malaria to two of its constituent clinical subphenotypes, severe malarial anaemia (SMA) and cerebral malaria (CM), the three deficiency alleles exhibited trends of opposing effect, with risk conferred to SMA and protection with respect to CM. To assess the overall effect of G6PD deficiency trait, deficiency alleles found across all three loci were pooled. G6PD deficiency trait was found to be significantly associated with protection from severe malaria overall (OR 0.83 [0.75–0.92], P = 0.0006 P = 0.0006 ), but this was limited to CM (OR 0.73 [0.61–0.87], P = 0.0005 P = 0.0005 ), with a trend toward increased risk for SMA, especially in fully-deficient individuals (OR 1.43 [0.99–2.08], P = 0.056 P = 0.056 ). Sex-stratified testing largely comported with these results, with evidence suggesting that protection by G6PD deficiency trait is conferred to both males and females, though susceptibility to SMA may be restricted to fully-deficient male hemizygotes. Conclusions In a part of Africa where multiple alleles contribute to expression of G6PD deficiency trait, these findings clarify and extend previous work done in populations where a single variant predominates, and taken together suggest a causal role for G6PD deficiency trait itself with respect to severe malaria, with opposing effects seen on two major clinical subphenotypes.